Comparison of Different Methods of Induction of Labour Methods; Khyber Pakhtunkhwa Perspective - Mahnaz Raees, Farnaz Zahoor, (Pakistan Journal of Medical & Health Sciences, 2023)
Objectives: to compare the mechanical, pharmacological or combination of both in induction of labour. Methods: This comparative observational study was conducted in Department of Obs and Gynae, Lady Reading Hospital, from January 2019 to December 2019. In this study all women presenting to labor room with singleton pregnancy and gestational age > 37 weeks and admitted for induction of labor were included. All those women with multiple pregnancies, premature rupture of membrane, malpresentation, and prior Cesareans section were excluded. Total 300 patients were included in the study period, Patients were divided into 4 groups, Group A (mechanical methods), Group B (prostaglandin E2), Group C (mechanical + PGE2), Group D (misoprostol). Data were analyzed using IBM SPSS Statistics for Windows, Version 23.0 (IBM Corp., Armonk, NY). Results: In this study 300 patients were included, in mean age of 24.54±12 years, with age range of 16- 40 years. Majority were Primi gravida (167 (55.7%), and 99.7 had poor bishop score. Indication for induction of 109(36.3%) was due to eclampsia / pre-eclampsia, followed by postdate pregnancy 98(32.7%). In majority of cases 123(41%) time from induction to labour was 6-12 hours. prostaglandin group showed good success rate in term of normal vaginal delivery and low adverse effects and good maternal and neonatal outcomes, followed by misoprostol, lowest success rate was recorded in mechanical only group . (p<0.001) Conclusion: Our study concludes that among different methods available for induction of labour, PGE2 is safe, effective and have goof maternal and fetal outcomes Keywords: induction, labour, PGE2, misoprostol